2005
DOI: 10.1007/s00405-004-0903-0
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial abscesses associated with chronic suppurative otitis media

Abstract: Intracranial abscesses are serious complications of chronic suppurative otitis media (COM). This study included 32 patients presenting with intracranial abscesses from 780 patients hospitalized for treatment of COM. The 32 patients had 59 intracranial complications. Perisinus abscess (13 of 32) was the most common intracranial abscess, followed by temporal lobe abscess (8 of 32), epidural abscess (7 of 32), cerebellar abscess (6 of 32) and subdural empyema (2 of 32). Headache (93%), fever (87%) and altered men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 19 publications
1
37
1
6
Order By: Relevance
“…3), but has been reported as the third or fourth most common in other studies. [2,11,12] However, Mostafa et al also found that LST was the most common intracranial complication of COM, which is consistent with our series. [13] The gold standard radiological method for the diagnosis of LST is MR venography (Fig.…”
Section: Journal Of Medical Updatessupporting
confidence: 92%
See 3 more Smart Citations
“…3), but has been reported as the third or fourth most common in other studies. [2,11,12] However, Mostafa et al also found that LST was the most common intracranial complication of COM, which is consistent with our series. [13] The gold standard radiological method for the diagnosis of LST is MR venography (Fig.…”
Section: Journal Of Medical Updatessupporting
confidence: 92%
“…[13][14][15] Seven et al claimed that there was no difference between these two approaches. [2] The latest studies have revealed that removal of the infected granulation tissue, without thrombus, is sufficient for recanalization of the sinus. [2,14] In our study, all four patients with LST underwent radical mastoidectomy together with removal of the infected thrombus through an incision in the sinus wall.…”
Section: Journal Of Medical Updatesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common predisposing factor was infection of the middle ear and mastoid process (21.9%). PBA secondary to mastoiditis can be seen in recurrent fashion (25). Our experience of PBA secondary to mastoiditis treatment necessitated a team approach with otolaryngologists.…”
Section: Abscess Locationmentioning
confidence: 99%